Effortful control is associated with executive attention: A computational study. Issue 4 (16th January 2021) - Ossola, Paolo; Antonucci, Camilla; Meehan, Kevin B.; Cain, Nicole M.; Ferrari, Martina; Soliani, Antonio; Marchesi, Carlo; Clarkin, John F.; Sambataro, Fabio; De Panfilis, Chiara
Abstract: Introduction: Effortful control (EC) is the self‐regulatory aspect of temperament that is thought to reflect the efficiency of executive attention (EA). Findings on relationship between EC and performance on EA tasks among adults are still contradictory. This study used a computational approach to clarify whether greater self‐reported EC reflects better EA. Methods: Four hundred twenty‐seven healthy subjects completed the Adult Temperament Questionnaires and the Attention Network Task‐revised, a conflict resolution task that gauges EA as the flanker effect (FE), that is, the difference in performances between incongruent and congruent trials. Here we also employed a drift‐diffusion model in which parameters reflecting the actual decisional process (drift rate) and the extra‐decisional time are extracted for congruent and incongruent trials. Results: EC was not correlated with the FE computed with the classic approach, but correlated positively with drift rate for the incongruent trials, even when controlling for the drift rate in the congruent condition and the extra‐decisional time in the incongruent condition. Conclusion: This study demonstrates an association between self‐reported EC and EA among adults. Specifically, EC is not associated with overall response facilitation but specifically with a greater ability to make goal‐oriented decisions when facing conflicting information.